An Occupational Hazards and Health Related Issues of Cashew Workers in Cashew Nut Processing – A Review - A. , Sivasangari; G. , Sasikumar (International Journal of Psychosocial Rehabilitation, 2020)
Nowadays cashew nut cultivation and processing is a key area of agronomy. One-third of the worldwide trading for cashew nut production is accounted for by India. Uncomfortable sitting positions and direct touching with nutshell liquid may make the laborers exposed to various health issues. Female workers are involved in the cashew nut processing unit. This review was envisioned to know the occupational hazards and healthiness factors of women employees. The effort in the cashew nut industry is substantially high; musculoskeletal disorder and cardiovascular stress are also reported. Issues related to dermatological conditions are very much predominant amongst females involved in cashew trading. Female employees found a major division in cashew trading, and approximately 90% of the laborers in processing units are female. It is majorly reported that women suffer from respiratory problems, and musculoskeletal disorders are moderately high in the recent scenario of cashew nut processing. Hence, this review provides a survey of occupational hazards and health and environmental issues of cashew workers in the cashew industry.